Carbon-stabilized porous silicon as novel voltammetric sensor platforms. (1st May 2021) - Pérez-Ràfols, Clara; Guo, Keying; Alba, Maria; Toh, Rou Jun; Serrano, Núria; Voelcker, Nicolas H.; Prieto-Simón, Beatriz
Highlights: Carbon-stabilized porous silicon outperforms GCE as voltammetric sensor. Electrode catalytic enhancement harnessed to discriminate redox species. Simultaneous determination of three dihydroxybenzene isomers. Good reproducibility, high sensitivity and low LOD (all <5 µmol L −1 ). Good recovery in the analysis of water samples spiked with hydroquinone and catechol. Abstract: The use of carbon-stabilized porous silicon (pSi) as a voltammetric sensing platform able to discriminate the detection of various electroactive species with similar redox potentials is demonstrated for the first time. For this purpose, the voltammetric responses to the presence of the three dihydroxybenzene isomers hydroquinone, catechol and resorcinol were studied using thermally hydrocarbonized pSi (THCpSi) and thermally carbonized pSi (TCpSi), as well as a glassy carbon electrode (GCE) as a benchmark. Both THCpSi and TCpSi outperformed the electrochemical performance of a GCE, as shown by the electrochemical characterization performed in the presence of the redox pair [Fe(CN)6 ] 3-/4- . Cyclic voltammetry results demonstrated that both THCpSi and TCpSi exhibited fast electron transfer kinetics, with TCpSi showing a slightly improved electrochemical performance. The electrode catalytic enhancement shown by these carbon-stabilized nanostructures was harnessed to allow the simultaneous voltammetric determination of hydroquinone, catechol and resorcinol. The analytical performance of TCpSi to the detection of the three dihydroxybenzene isomers was studied using differential pulse voltammetry, revealing good reproducibility, high sensitivity, low limits of detection (all below 5 µmol L −1 ) and good recoveries (between 98 and 102%) in the analysis of spiked tap water samples. Graphical abstract: Image, graphical abstract